Pengaruh Selebgram Endorsement Dan Media Sosial Instagram Sebagai Media Promosi Untuk Meningkatkan Minat Beli Produk Make Over (Studi kasus pada remaja di Kota Malang) - Adis Fransiska Romadhon; Jeni Susyanti; Achmad Agus Priyono (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
AbstractThis research was conducted in Malang City. The type of research used is explanatory research with a quantitative approach. The purpose of this study was to determine the effect of endorsements and Instagram on buying interest. The independent variables used are endorsement and instagram, while the dependent variable is buying interest. The sample used in this study were 80 respondents who were consumers of Make Over products. Data collection techniques using a questionnaire. The analytical method used is the instrument test, multiple linear regression analysis, classical assumption test, determination test, f test and t test using SPSS 16.0 computer software for data processing. The results of this study indicate that endorsement has an effect on buying interest, and Instagram has an effect on buying interest. Endorsements and Instagram simultaneously affect buying interest. Keywords: Endorsement, Instagram and Buying Interest